Prospective comparison of transperineal magnetic resonance imaging/ultrasonography fusion biopsy and transrectal systematic biopsy in biopsy‐naïve patients. (15th October 2017) - Borkowetz, Angelika; Hadaschik, Boris; Platzek, Ivan; Toma, Marieta; Torsev, Georgi; Renner, Theresa; Herout, Roman; Baunacke, Martin; Laniado, Michael; Baretton, Gustavo; Radtke, Jan Philipp; Kesch, Claudia; et al.
Abstract : Objectives: To evaluate the value of multiparametric magnetic resonance imaging (mpMRI) in the detection of significant prostate cancer (PCa) and to compare transperineal MRI/ultrasonography fusion biopsy (fusPbx) with conventional transrectal systematic biopsy (sysPbx) in biopsy‐naïve patients. Patients and Methods: This multicentre, prospective trial investigated biopsy‐naïve patients with suspicion of PCa undergoing transperineal fusPbx in combination with transrectal sysPbx (comPbx). The primary outcome was the detection of significant PCa, defined as Gleason pattern 4 or 5. We analysed the results after a study period of 2 years. Results: The study included 214 patients. The median (range) number of targeted and systematic cores was 6 (2–15) and 12 (6–18), respectively. The overall PCa detection rate of comPbx was 52%. FusPbx detected more PCa than sysPbx (47% vs 43%; P = 0.15). The detection rate of significant PCa was 38% for fusPbx and 35% for sysPbx ( P = 0.296). The rate of missed significant PCa was 14% in fusPbx and 21% in sysPbx. ComPbx detected significantly more significant PCa than fusPbx and sysPbx alone (44% vs 38% vs 35%; P < 0.005). In patients presenting with Prostate Imaging Reporting and Data System (PI‐RADS) 4 and 5 lesions there was a higher detection rate of significant PCa than in patients presenting with PI‐RADS ≤3 lesions in comPbx (61% vs 14%; P < 0.005). Conclusions: For biopsy‐naïve men with tumour‐suspicious lesions in mpMRI, the combined approach outperformed both fusPbx and sysPbx in the detection of overall PCa and significant PCa. Thus, biopsy‐naïve patients may benefit from sysPbx in combination with mpMRI targeted fusPbx.